Symptoms and risk factors of Cryptosporidium hominis infection in children: data from a large waterborne outbreak in Sweden - Adler, Sara (Parasitol Res, 2017)
Cryptosporidium is a major cause of diarrheal disease worldwide. In developing countries, this infection is endemic and in children, associated with growth faltering and cognitive function deficits, with the most severe impact on those aged <2 years. Little has been reported about symptoms and risk factors for children in industrialized countries, although the disease incidence is increasing in such regions. In November 2010, a large waterborne outbreak of C. hominis occurred in the city of Östersund in Sweden. Approximately 27,000 of the 60,000 inhabitants were symptomatic. We aimed to describe duration of symptoms and the risk factors for infection with C. hominis in children aged <15 years in a Western setting. Within 2 months after a boil water advisory, a questionnaire was sent to randomly selected inhabitants of all ages, including 753 children aged <15 years. Those with ≥3 loose stools/day were defined as cases of diarrhoea. The response rate was 70.3%, and 211 children (39.9%) fulfilled the case definition. Mean duration of diarrhoea was 7.5 days (median 6, range 1–80 days). Recurrence, defined as a new episode of diarrhoea after ≥2 days of normal stools, occurred in 52.5% of the cases. Significant risk factors for infection, besides living within the distribution area of the contaminated water plant, included a high level of water consumption, male sex, and a previous history of loose stools. The outbreak was characterized by high attack and recurrence rates, emphasizing the necessity of water surveillance to prevent future outbreaks.